Two new species of Omyomymar Schauff (Hymenoptera: Mymaridae) from the Indian Himalayan Region with a key to Indian species - Anwar, Prince Tarique; Zeya, Shahid Bin; Usman, Syeda Uzma (EntomoBrasilis, 2021)
Two new species of the genus Omyomymar Schauff (Hymenoptera: Mymaridae), Omyomymar sudhiri sp. nov. Anwar & Zeya and Omyomymar supremus sp. nov. Anwar & Zeya are described from the Indian Himalayan regions. An identification key to Indian species is provided. All the previously recorded and described species of the genus are analyzed and discussed.